2017
DOI: 10.1371/journal.pone.0187803
|View full text |Cite
|
Sign up to set email alerts
|

Performance of DNA metabarcoding, standard barcoding, and morphological approach in the identification of host–parasitoid interactions

Abstract: Understanding interactions between herbivores and parasitoids is essential for successful biodiversity protection and monitoring and for biological pest control. Morphological identifications employ insect rearing and are complicated by insects’ high diversity and crypsis. DNA barcoding has been successfully used in studies of host–parasitoid interactions as it can substantially increase the recovered real host–parasitoid diversity distorted by overlooked species complexes, or by species with slight morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 61 publications
0
43
0
1
Order By: Relevance
“…The public availability of DNA barcodes will facilitate future forensic studies on host‐parasitoid associations and serves as the foundation upon which additional species can be added to improve the utility of this tool for analysis of trophic interactions between native and exotic species in this system. Future studies employing next‐generation DNA sequencing (NGS) or metabarcoding could make use of these sequence data to characterize all possible trophic interactions simultaneously, as has been shown in aphid‐parasitoid associations (Lefort, Wratten, Cusumano, Varennes, & Boyer, ) and in host‐parasitoid associations in forest dwelling Lepidoptera and Hymenoptera (Šigut et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The public availability of DNA barcodes will facilitate future forensic studies on host‐parasitoid associations and serves as the foundation upon which additional species can be added to improve the utility of this tool for analysis of trophic interactions between native and exotic species in this system. Future studies employing next‐generation DNA sequencing (NGS) or metabarcoding could make use of these sequence data to characterize all possible trophic interactions simultaneously, as has been shown in aphid‐parasitoid associations (Lefort, Wratten, Cusumano, Varennes, & Boyer, ) and in host‐parasitoid associations in forest dwelling Lepidoptera and Hymenoptera (Šigut et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies have demonstrated the utility of these approaches for detecting species interactions, although see Lefort, Wratten, Cusumano, Varennes, and Boyer () and Šigut et al. () for examples of parasitism using more conventional sample tracking methods.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this method has also several problems, such as a lack of direct evidence of the cause of death, prey mobility, or requirement for mass rearing of the prey (Kneib & Scheele, ; Molleman et al, ). For evidence of parasitism of the exposed host, the host must be kept until the adult stage, dissected for the presence of parasitoid larvae, or screened by molecular detection methods (Franck et al, ; Šigut et al, ).…”
Section: Introductionmentioning
confidence: 99%